1980
DOI: 10.3133/pp1132
|View full text |Cite
|
Sign up to set email alerts
|

Recent vegetation changes along the Colorado River between Glen Canyon Dam and Lake Mead, Arizona

Abstract: Introduction ____________________________________ 1 Acknowledgments ____________________________________ 3 Changes in Colorado River streamflow regime ________ 3 Floods _________________________________ 3 Daily stage.__________________________ 6 Annual discharge_________________________ 7 Monthly discharge __________ _______________________? Changes in channel and alluvial deposits in the Colorado River below Glen Canyon Dam ______________________ 8 A history of photography on the Colorado River __________ 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
160
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 10 publications
8
160
0
Order By: Relevance
“…For instance, in the Grand Canyon, the beaver population has likely increased since the construction of Glen Canyon Dam, putatively because controlled flows from the dam beginning in 1963 led to higher primary and secondary production in riparian ecosystems (Turner andKarpiscak 1980, Kearsley et al 2006). Numerous studies have shown that riparian vegetation has increased in the Grand Canyon since flow regulation primarily because of the elimination of annual flood events that scoured shorelines (Turner and Karpiscak 1980, Stevens et al 1995. For instance, the area of riparian vegetation has increased by more than 50% and continues to expand , and marsh communities have expanded throughout the corridor (Stevens et al 1995).…”
mentioning
confidence: 99%
“…For instance, in the Grand Canyon, the beaver population has likely increased since the construction of Glen Canyon Dam, putatively because controlled flows from the dam beginning in 1963 led to higher primary and secondary production in riparian ecosystems (Turner andKarpiscak 1980, Kearsley et al 2006). Numerous studies have shown that riparian vegetation has increased in the Grand Canyon since flow regulation primarily because of the elimination of annual flood events that scoured shorelines (Turner and Karpiscak 1980, Stevens et al 1995. For instance, the area of riparian vegetation has increased by more than 50% and continues to expand , and marsh communities have expanded throughout the corridor (Stevens et al 1995).…”
mentioning
confidence: 99%
“…However, the existence and operation of Glen Canyon Dam had additional incidental, though very significant, physical and ecological effects upon the Colorado River downstream through Grand Canyon National Park, Both the aquatic and riparian communities have been substantially altered by the invasion of exotic species more adapted to colder, clearer water and less variable flows than the native species (Turner & Karpiscak, 1980;Minckley, 1991). These issues and others are discussed extensively in Marzolf (1991).…”
mentioning
confidence: 99%
“…Thus, unlike alluvial rivers, the location of sandbars in the geomorphically constrained Colorado River are fixed within 13 geomorphic reaches (Table 2). More than 550 debris fan complexes generate a distinctive suite of fluvial microhabitats, each with discrete grain sizes, soils, stage elevation relationships, inundation frequencies, and stage-zoned riparian vegetation (Turner and Karpiscak 1980;Schmidt and Graf 1990;Melis et al 1997). Analyses of flow regulation influences at a large suite of debris fan complexes revealed that flow regulation allowed extensive development of fluvial marshes, enhancing riverine plant species richness (Stevens et al 1995;Waring et al in press).…”
Section: Geology and Geomorphologymentioning
confidence: 99%